Galα1-4Galβ1-3GalNAc is the dominant epitope of Em2 antigen, the mucin-type glycoprotein from Echinococcus multilocularis - Yamano, Kimiaki; Koizumi, Akihiko; Takeda, Tadahiro; Kiuchi, Fumiyuki; Hada, Noriyasu (Parasitology research (1987), 2012)
The larval stage of Echinococcus multilocularis causes alveolar echinococcosis in human. In serodiagnosis of alveolar echinococcosis, specific reactions have been noted not only against protein antigens but also carbohydrates. With regard to protein antigens, the recent development of recombinant antigens has contributed to an improvement in serodiagnostic examination. On the contrary, the preparation of carbohydrate antigen still depends on extraction from crude antigens, and isolation is usually accompanied with difficulty; consequently, it is rare to examine individual antigenicity of carbohydrates. However, parasitic helminths express various antigenic carbohydrates. In the case of Echinococcus granulosus , antigenic glycoproteins of the laminated layer have been reported. Furthermore, the laminated layer of E. multilocularis contains Em2 antigen which is a famous mucin-type glycoprotein and which seems to play an important role in metacestode survival mechanisms within the immunologically reacting host; nevertheless, the anomeric configurations and the individual antigenicity of Em2 O -glycans have not been confirmed so far. Under these circumstances, we introduced a chemical synthesis to get pure oligosaccharides in order to assess diagnostic performance. In our previous study, 11 oligosaccharides have already been prepared by stereocontrolled syntheses. Among them, three synthetic oligosaccharides showed antigenicity. Our aim is to investigate correct sequence and serodiagnostic potential of the dominant epitope of Em2. This study provided important diagnostic information: (1) the trisaccharide Galα1-4Galβ1-3GalNAc sequence is the dominant epitope of Em2 (sensitivity 95.0 %), (2) Trematoda expresses carbohydrates with the similar trisaccharide sequence, and (3) the terminal Galα1-4Gal sequence is a candidate for the widely common epitope that accounts for the cross-reaction.